STRATEGI MEDIA RELATIONS BRANCH COMMUNICATION PT ANGKASA PURA II BANDARA KUALANAMU DALAM MENINGKATKAN CITRA POSITIF PERUSAHAHAAN - Annisa Afriani; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Branch Communiation is a connecting bridge between a company with society. So that Public Relation practicioner of PT. Angkasa Pura II (Persero) keep on trying to build positive sinergy with media in order to increase positive image. Kualanamu Airport is one of majestic icon at Sumatera Utara which continuosly gain 4 star Skytrax in three times. Despite building a lot of cooperation with media doesn’t promises that the news will always positive, but also there is some negative news which interestingly packed but cornering the company at the other side.This research using descriptive qualitative method. Subject determine with purposive and accidental sampling technique. Informant in this research is Branch Communication Manager, Branch Communication Assistant Manager PT. Angkasa Pura II Kualanamu Airport, 4 media that often covers Kualanamu and also 4 Kualanamu Airport users. Data collection with interview, observation, and documentation. Data analisys use the model interactive data analys Miles and Huberman. The validation of data uses an extention of participation and triangulation. Result of this research shown that media relations strategy which Branch Communication PT. Angkasa Pura II Kualanamu Airport in order to increase positive image concern 3 things. Strategy to develop relation is creating Whatsapp Group “KNO media community” to make communication acces easier. And also make activities with media like coffee morning, gathering, press conference, press luncheon and others. In developing strategy, Branch Communication also join various seminars to expand public relation with mass media, fast response to provide information and clarification to media crew, Tour Kualanamu use networking media. And strategy in developing networks by the Branch Communication is done by having good relationship with Persatuan Wartawan Indonesia (PWI), Ikatan Jurnalis Televisi Indonesia (IJTI) and will join PERHUMAS Sumatera Utara which has vacum for a long time. And so the obstacles faced during a relationship with media crew is the information from buzzer on uncredible social media, so that negative news will often occurred without clarification from airport side. And so there is sarcasm clickbait that often use by media crew that will easily draw attention of society to read and affect them. Keyword: Media Relation Strategy, Branch Communication PT Angkasa Pura II Kualanamu Airport, company positif image.